2004
DOI: 10.3748/wjg.v10.i9.1297
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid uptake in arterio-venous serum of normal and cancerous colon tissues

Abstract: Abnormal synthetic metabolism of colon cancer may contribute to its higher amino acid uptake rate than that of normal colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…These findings are in accordance with previous reports where an increase in amino acid turnover in breast cancer is reported [ 33 ]. In contrast, lower concentrations of various amino acids were observed in IDC serum, which is in agreement with previous report ( Supplementary Table 2 ) [ 34 ]. The diminished concentrations of the amino acids in IDC serum may be attributed to their higher uptake by the tumour tissue to fulfil the proliferative demand [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in accordance with previous reports where an increase in amino acid turnover in breast cancer is reported [ 33 ]. In contrast, lower concentrations of various amino acids were observed in IDC serum, which is in agreement with previous report ( Supplementary Table 2 ) [ 34 ]. The diminished concentrations of the amino acids in IDC serum may be attributed to their higher uptake by the tumour tissue to fulfil the proliferative demand [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…Increase in fatty acids in both serum and tissue is indicative of their de-novo synthesis in serum and uptake in tissue to support proliferation [ 49 ]. As discussed above, the lower levels of the amino acids in IDC serum could be due to their increased uptake by the tumour tissue leading to their accumulation in tissue and deprival in serum [ 34 ]. Other important metabolic changes shared by both tissue and serum were involved in antioxidant machinery, energy metabolism etc.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the report that cancer cells may take up more essential amino acids [8]. The 875 cm -1 Raman peak due to hydroxyproline (a compound of collagen), and the 1445 cm -1 peak (associated with the CH 2 CH 3 bending modes of collagen), shows higher signals in cancer than in normal, confirming that the amount of collagen is increased in cancer tissue due to a desmoplastic response [6,8]. The Raman peak at 1320 cm -1 , associated with CH 3 CH 2 twisting mode of collagen/lipids, as well as the 1656 cm -1 peak, associated with the protein amide I band of collagen, being higher in cancer spectra further confirms the change of molecular structures like the deposition of greater amounts of collagen in cancer tissue compared to normal tissue [6].…”
Section: Discussionsupporting
confidence: 93%
“…For instance, the Raman peak of 1002 cm -1 which is associated with phenylanaline shows a higher signal in cancer tissue, indicating an increase in the essential amino acid phenelanaline relative to the total Raman-active components in the cancer tissue. This is consistent with the report that cancer cells may take up more essential amino acids [8]. The 875 cm -1 Raman peak due to hydroxyproline (a compound of collagen), and the 1445 cm -1 peak (associated with the CH 2 CH 3 bending modes of collagen), shows higher signals in cancer than in normal, confirming that the amount of collagen is increased in cancer tissue due to a desmoplastic response [6,8].…”
Section: Discussionsupporting
confidence: 90%
“…For instance, Ala and Pro are biosynthesized from Glu via aminotransferase [ 53 ]. Tumor growth requires Glu, Gly, Asp and ammonia for purine and pyrimidine synthesis, which brings a selective demand on these metabolites [ 54 ]. Actually, our data showed that the levels of these amino acids in patients with different cancers were lower than those of healthy individuals.…”
Section: Discussionmentioning
confidence: 99%